2021
DOI: 10.1038/s41598-021-89475-y
|View full text |Cite
|
Sign up to set email alerts
|

Metformin improves the outcomes in Chinese invasive breast cancer patients with type 2 diabetes mellitus

Abstract: Early reports indicate that metformin, a clinical drug administered to treat type 2 diabetes mellitus (T2DM), was found to be associated with a better prognosis of cancer. The objective of this study was retrospectively analyzed the effect of metformin on the outcomes of Chinese breast cancer patients with T2DM. A total of 3757 primary invasive breast cancer patients who underwent surgery from January 2010 to December 2013 were enrolled. According to the medication treatment, all the patients were divided as n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Clearly, it has a high increase rate and spreads around the globe, especially in rich places, such as South America and Middle East. Although many chemical diabetes detection methods are reported, invasive , and non-invasive type, , exploring a novel, fast, convenient, accurate, and non-invasive type physical method is challenging but meaningful. Results of this study have proved that the solidification characteristics of urine droplet could be used to reflect the compositions in urine.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, it has a high increase rate and spreads around the globe, especially in rich places, such as South America and Middle East. Although many chemical diabetes detection methods are reported, invasive , and non-invasive type, , exploring a novel, fast, convenient, accurate, and non-invasive type physical method is challenging but meaningful. Results of this study have proved that the solidification characteristics of urine droplet could be used to reflect the compositions in urine.…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective cohort study of 3553 patients with breast cancer and DM showed significant survival differences among the non-diabetes group, metformin group, and insulin group; the five-year disease-free survival rate (DFS) was 85.8%, 96.1%, and 73.0%, and the five-year overall survival (OS) was 87.3%, 97.1%, and 73.3%, respectively. This provides a theoretical background for introducing metformin for the treatment of cancer and improving the overall survival rate [56].…”
Section: Metforminmentioning
confidence: 99%
“…A recent Chinese prospective observational study of almost 4000 patients with incident breast cancer showed significant survival differences favoring metformin. In contrast, the use of insulin was associated with decreased survival compared with the non-diabetes group [ 83 ].…”
Section: Cancermentioning
confidence: 99%
“…In summary, there is strong observational evidence that metformin may reduce the incidence of breast cancer, in particular estrogen-positive tumors [ 78 , 81 , 86 ]. Additionally, in patients diagnosed with breast cancer, metformin was associated with lower risk of a second breast tumor, recurrence or breast-cancer-related death [ 82 , 83 ]. However, randomized trials in metastatic disease and recurrent breast cancer fail to show a benefit of metformin as adjunctive therapy [ 88 , 89 ].…”
Section: Cancermentioning
confidence: 99%